In vitro Antioxidant and in vivo Hepatoprotective Activities of Root Bark Extract and Solvent Fractions of Croton macrostachyus Hochst. Ex Del. (Euphorbiaceae) on Paracetamol-Induced Liver Damage in Mice - Tafere GG; Tuem KB; Gebre AK; Balasubramaniam R (Dove Medical Press, 2020)
Gebrehiwot Gebremedhin Tafere,1 Kald Beshir Tuem,1 Abadi Kahsu Gebre,1 Rajkapoor Balasubramaniam1,2 1Department of Pharmacology and Toxicology, School of Pharmacy, College of Health Sciences, Mekelle University, Mekelle, Ethiopia; 2Department of Pharmacology, JKK Nattraja College of Pharmacy, Komarapalayam 638 183, Tamilnadu, IndiaCorrespondence: Kald Beshir Tuem Tel +251920425426Email kalizad2003@gmail.comBackground: Liver disease is a major public health threat, particularly in developing countries. Several medicinal plants and formulations have been claimed to have liver protective activities. The present study aimed to evaluate in vitro antioxidant and in vivo hepatoprotective activities of root bark extracts of Croton macrostachyus (Euphorbiaceae).Methods: Free radical scavenging activity of crude extract and solvent fractions of the plant was conducted using the DPPH assay method. Hepatoprotective activities of the crude extract and solvent fractions of the plant were carried out based on paracetamol-induced liver damage in mice. Serum biomarkers (AST, ALT, ALP, total bilirubin and total protein) were assessed to find out the effect. Histopathological examination was also carried out for all groups of mice to further confirm the findings.Results: Antioxidant assay revealed that the crude extract, aqueous fraction and chloroform fraction of Croton macrostachyus exhibited free radical scavenging activity with IC50 values of 128.6, 168.9, and 406 μg/mL, respectively. Pretreatment of the mice with the crude extract and solvent fractions of Croton macrostachyus significantly reduced ALP (p< 0.001), ALT (p< 0.001), and AST (p< 0.001) levels at all the administered doses compared to the toxic group. The crude extract and chloroform fraction decreased total bilirubin level at doses of 200 mg/kg (P< 0.05) and 400 mg/kg (P< 0.001). Pretreatment of the mice with 400 mg/kg of the crude extract and aqueous fraction elevated total protein value compared to the paracetamol treated group (P< 0.05). The hepatoprotective activities of the plant extracts were confirmed by histopathological studies.Conclusion: From this study, it can be concluded that the crude extract and solvent fractions of Croton macrostachyus demonstrated antioxidant and hepatoprotective activities.Keywords: antioxidant, hepatoprotective, Croton macrostachyus, paracetamol, biochemical parameters, liver damage